SynergisticCombinationofCiplukan(Physalis angulata) HerbsEthanolicExtractandDoxorubicinonT47DBreast CancerCells - Armandari, Inna; Palupi, Kartika Dyah; Farida, Sofa; Hermawan, Adam; Susidarti, Ratna Asmah; Meiyanto, Edy (Indonesian Research Gateway, 2010)
Doxorubicinisoneofchemotherapeuticagentwidelyusedinbreastcancertreatment,but in high dose doxorubicin gives negative side effect, including vomit, nausea, immune suppression, and cardiac toxicity. This toxicity hopefully could be reduced by combination chemotherapy using natural herbs such as ciplukan herb. This research was conducted to explorecytotoxicactivityofsingleciplukanherbsethanolicextractanditscombinationwith doxorubicinonT47Dbreastcancercells.Cytotoxicactivityofciplukanherbsethanolicextract only and its combination with doxorubicinwere tested on T47D cells using MTT assay toobtainIC50valueandcombinationindex(CI),respectively.Singleextractshowedcytotoxic activityonT47DcellswithIC50valueofwas160*g/ml.Thus,combinationtreatmentfrom ciplukanherbsethanolicextractanddoxorubicinshowedsynergisticeffect(CI<1,0).Thiseffect wasreachedatconcentrationofciplukanherbsethanolicextract-doxorubicin80ÃÂ¼g/ml-2nM, 80 ÃÂ¼g/ml-4 nM, and 80 ÃÂ¼g/ml-8 nM. This research indicated that ciplukan herbs ethanolic extractispotentialtobeappliedasco-chemotherapeuticagentinbreastcancertherapy.